SEJARAH KESULTANAN BILAH KABUPATEN LABUHANBATU PROVINSI SUMATERA UTARA TAHUN 1630-1945 - Meila Ningsih; Drs. Ridwan Melay, M.Hum; Drs. Kamaruddin,M.Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : the purpose of this research is (1) To know the History of Sultanate Bilah (2) To know a period of determine heyday Sultanate Bilah of Sultan Musa Bidar Alamsyah (3) To know to collapse of the Sultanate Bilah (4) To know the ommission from Sultanate Bilah. The benefit of this research are (1) To application of writer science for sitting bench lecture, adding writer knowledge about local history (2) To reach for the Bachelor of Education at Faculty Teachership and Science Education at University of Riau (3) As reference source for reader, governmental and North Sumatra society, specially society of Regency Labuhanbatu about history of Sultanate Bilah utilize to equip the local history article (4) As Erudite Masterpiece contribution for library in Faculty Teachership and Education Science, specially for library The Study of history Education at University of Riau (5) As medium of information and reference substance for the research of hereinafter which deal with same problem, specially for History student. In this research use the research method Qualitative. Result from this research is Sultanate Bilah represent a Sultanate which have stood in Old Country Countryside of Subdistrict Bilah Go Downstream The Regency of Labuhanbatu Province of North Sumatra in year 1630. A period Heyday of Sultanate Bilah in year 1860, at period governance of Sultan Musa Bidar Alamsyah (Bidar Alam III) visible in so many aspect, like Governance, Social, Economic, Culture And Religion. A period of retreating or collapse of the Sultanate Bilah in year 1945 at period governance of Sultan Adil Bidar Alamsyah (Bidar Alam V). Factor causing to collapse of the Sultanate Bilah because of some factor influencing it so that Sultanate Bilah by degrees lost ground.Key Words : History, Sultanate Bilah